Democracy and FDI - Matthias Busse (Hamburg Institute of International Economics (HWWA), 2003)
Many believe that multinational enterprises insensitively ignore political rights and civil liberties in the countries of their investments. Frequently, non-governmental organisations accuse multinationals of fostering repressive regimes in developing countries and consider foreign direct investment (FDI) as a tool of exploitation. This paper tries to examine empirically the complex relationship between democracy and FDI in a systematic way, using cross-sectional and panel data analysis. The results indicate that – on average – investments by multinationals are significantly higher in democratic countries, thereby refuting the hypothesis that political repression fosters FDI. Yet this positive link does not hold for the 1970s, when a considerable share of FDI flowed to countries with repressive regimes.
Keywords: F21; F23; C31; C33; 330; FDI; Democracy; Political Rights; Civil Liberties; Direktinvestition; Multinationales Unternehmen; Demokratie; Menschenrechte; Schätzung; Welt